Design and Validation of a Parent-Adolescent Educational Package Based on Their Lived Experiences - Atashsokhan , Mina; Abolmaali Alhosseini , Khadijeh; Bagheri, Nasrin (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2024)
Objective: The aim of this study was to design and validate a parent-adolescent educational package based on the lived experiences of parents and adolescents. Methods and Materials: This research was conducted with a qualitative approach using thematic analysis. Participants included mothers and adolescent girls from lower secondary school in Tehran. Data were collected and analyzed through semi-structured interviews. To validate the parent-adolescent educational package, the content validity ratio (CVR) and content validity index (CVI) were examined based on the opinions of ten experts. Findings: The findings indicated that the designed educational package could enhance positive communication between parents and adolescents, improve academic performance, and promote the mental health of adolescents. The package included various educational sessions, each specifically addressing topics such as conflict management, negotiation and effective communication, and the development of adolescent self-efficacy. The validity indices of the package all showed numbers higher than 0.75, indicating high validity. Conclusion: The results suggested that the parent-adolescent educational package could serve as an effective tool for improving and strengthening the relationship between parents and adolescents, helping them better manage the challenges of adolescence. These results underscore the need to integrate family education programs in schools and educational centers to strengthen family communication foundations.